2023
DOI: 10.1039/d3qi01257c
|View full text |Cite
|
Sign up to set email alerts
|

Na6Sn3P4S16: Sn(ii)-chelated PS4 groups inspired an ultra-strong SHG response

Chenyao Zhao,
Bingbing Zhang,
Xinyu Tian
et al.

Abstract: Discovery of new infrared nonlinear optical (IR NLO) materials with large second harmonic generation (SHG) effect and broad optical bandgap is still a challenging work. Based on this, we have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…6 The addition of stereochemically-active-lone-pair (SCALP) cations, like As 3+ , Sb 3+ , Bi 3+ , Sn 2+ , and Pb 2+ , to chalcogenide systems has attracted the most attention among all the feasible approaches for creating IR-NLO materials because the majority of these chalcogenides exhibit exceptional IR-NLO performances. 7 Among these cations, Pb 2+ makes a significant contribution to the d eff but adversely affects the optical E g . 8 As is known, narrow energy gaps ( E g < 2.33 eV) are unable to mitigate some harmful two-photon or free-carrier absorption under fundamental 1064 nm laser sources.…”
Section: Introductionmentioning
confidence: 99%
“…6 The addition of stereochemically-active-lone-pair (SCALP) cations, like As 3+ , Sb 3+ , Bi 3+ , Sn 2+ , and Pb 2+ , to chalcogenide systems has attracted the most attention among all the feasible approaches for creating IR-NLO materials because the majority of these chalcogenides exhibit exceptional IR-NLO performances. 7 Among these cations, Pb 2+ makes a significant contribution to the d eff but adversely affects the optical E g . 8 As is known, narrow energy gaps ( E g < 2.33 eV) are unable to mitigate some harmful two-photon or free-carrier absorption under fundamental 1064 nm laser sources.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons showed these bandgaps of NMPS and RMPSC to be also much larger than those of some commercial sulphides, including AGS (2.73 eV), the phosphide ZnGeP 2 (1.75 eV), and most thiophosphates, including LiZnPS 4 , AgZnPS 4 59 —and showed the bandgap of Na 6 Mg 3 P 4 S 16 to be larger than those of other alkaline-earth-metal-based thiophosphates and that of Na 6 Sn 3 P 4 S 16 . 60 The results indicated that the [MgS 6 ] octahedra can generate a wider bandgap than can the other alkaline-earth metals. The wider bandgap of RMPSC than of NMPS may be attributed to the higher electronegativity of Cl ( χ = 2.58) than of S ( χ = 3.16).…”
mentioning
confidence: 98%
“…27 The above strategies suggest that the discovery of novel IR NLO materials is possible via rational structure consideration. Recently, metal thiophosphates with rich structures have been studied as NLO materials, including but not limited to KAg 2 PS 4 , 28 Na 6 Sn 3 P 4 S 16 , 29 and CuZnPS 4 . 30 These thiophosphates with excellent NLO properties can be attributed to the following aspects.…”
mentioning
confidence: 99%
“…The IR spectra (Figure 2b) of 1−4 show that their transparency covers the two IR atmospheric windows and the IR peak (∼700 cm −1 ) is assigned to the vibration absorption of P−S bonds. 29,47,48 The test results of differential scanning calorimetry (DSC) show that only one endothermic peak at 823.5 °C and one exothermic peak at 737.1 °C exist during the whole heating/ cooling process (Figure S6), and the X-ray diffraction analysis result after DSC measurement indicates congruent melting behavior of 1 (Figure S7).…”
mentioning
confidence: 99%